Aplikasi Asap Cair Sebagai Bahan Pengawet Terhadap Kualitas Minyak Goreng Pabrikan - Tulit Pati , Maria Astria ; Leki , Marianus Maroan ; Iskandar , Taufik ; Abrina, Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Cooking oil is one of the nine basic human needs in meeting daily needs. Repeated use of manufacturer cooking oil with high heating can cause oxidation in the oil which can cause the oil composition to change and produce compounds that have a rancid odor. This study aims to determine the optimal amount of frying in the manufacturer's cooking oil that has been added with liquid smoke for tofu frying. The liquid smoke of rice husk is obtained from the process of pyrolysis of rice husk which contains components of cellulose, hemicellulose, and lignin which produce phenol compounds, acid compounds and their derivatives, which can be used as antioxidants to prevent rancidity in the manufacturer's cooking oil. The parameters used in the analysis of the quality of the manufacturer's cooking oil are tests of free fatty acid levels, acid numbers, and peroxide numbers. The results showed that cooking oil was still suitable for use until the fourth frying time. The most effective volume of liquid smoke was 27 ml.